The Differences in Employees' Green Behavior Between Gender at PT Dewa Patria - Ardhillah Jenny; Dina Mellita; Fitriasuri; Efan Elpanso (TALENTA Publisher, Universitas Sumatera Utara, 2025)
This research aims to determine the effect of environmentally friendlyrecruitment selection, environmentally friendly training, environmentallyfriendly performance management, environmentally friendly payments &rewards, and environmentally friendly involvement on employee green behavior.The method used is quantitative. The purpose of this study is to examine theimpact of gender differences on employees' green behavior at PT Dewa Patria.This research employs a quantitative method with descriptive analysistechniques. The sample consists of 88 employees from PT Dewa Patria. Datacollection was conducted by distributing questionnaires to the employees. Dataanalysis involved normality tests and difference tests. The results indicate asignificant statistical difference in green behavior among employees based ongender. In other words, gender has a significant impact on employees' greenbehavior.